Altered T-Cell Receptor β-Chain and Lactate Dehydrogenase Are Associated With the Immune Pathogenesis of Biliary Atresia - Ye, Jing; Lai, Dengming; Cao, Dan; Tan, Linhua; Hu, Lei; Zha, Hua; Yang, Jiezuan; Shu, Qiang (Frontiers in Medicine, 2021)
Background: Biliary atresia (BA) is considered to be an autoimmune-mediating inflammatory injury. The pathogenesis of BA has been proposed with the clonal transformation of T cells expressing analogous T-cell receptor β-chain variable regions (TRBVs). Methods: The TRBV profile of the peripheral blood mononuclear cells (PBMCs) in infants with BA and control infants (healthy donors, HDs), respectively, were characterized by using high-throughput sequencing (HTS). The diversity of T cells was analyzed based on the frequency of complementarity-determining region 3 (CDR3) or V(CDR3)J. Moreover, the correlation between absolute lymphocyte count (ALC) and lactate dehydrogenase (LDH) or diversity (clonality) indices, respectively, were analyzed for subjects with BA and HD. Results: The diversity indices of CDR3, V(CDR3)J in BA are lower than those in subjects with HD, in addition, there are significantly different levels of neutrophile, neutrophile/lymphocyte ratio (NLR), and LDH between groups of BA and HD. The correlation between ALC and diversity index is significant in subjects with HD but is not for subjects with BA. Conversely, the relationship between ALC and LDH is significant in subjects with BA but is not for subjects with HD. Moreover, 12 CDR3 motifs are deficient or lower expression in BA compared with that in the HD group. Conclusion: Our results demonstrate that the profile of TRBV repertoire is significantly different between subjects with BA and HD, and suggest that the immune imbalance and elevated LDH level are associated with the pathogenesis of BA. Moreover, the values of neutrophile, NLR, and LDH could be used for the differential diagnosis of BA.